Critical analysis of methodological quality of systematic reviews and meta-analysis of antibiotics in third molar surgeries using AMSTAR 2 - Ankita Chugh; Arun Kumar Patnana; Pravin Kumar; Vinay Kumar Chugh; Daisy Khera; Surjit Singh (Journal of Oral Biology and Craniofacial Research)
The clinicians usually prescribe antibiotics to reduce post-operative complications during third molar surgeries. However, in the absence of clear conclusions regarding the use of antibiotics in third molar surgeries, present systematic review was planned to assess the quality of systematic reviews evaluating the efficiency of antibiotics in reducing post-operative complications. The literature search was done in Cochrane Library, Cochrane Central Register of Controlled Trials (CENTRAL), PUBMED, EMBASE, and Google scholar. Systematic reviews published in English during the period from January 1990 to December 2019 were included. The maxillary and mandibular third molars indicated for extraction either because of infection, orthodontic or prophylactic reasons were included. From 526 screened studies, thirteen reviews were qualified for qualitative analysis. The qualities of the included reviews were evaluated using the AMSTAR 2 tool. The included reviews were also evaluated based on the number of authors, geographic region, impact factor of the published journal, year of publication, and the number of citations for each review. One high quality, eight moderate quality, three low quality, and one critically low-quality reviews were observed in the present review. No statistically significant difference was observed between the included reviews based upon the analysis of the number of authors, geographic region, impact factor of the published journal, year of publication, and the number of citations for each review. Considering the observations form the high and moderate-quality reviews, the present systematic review concludes that antibiotics effectively aid in reducing the post-operative complications and frequency of observation of dry socket.